Determinants of Consumer Participation in Hobby-Based Online Secondary Markets: Evidence from Gen Z and Millennials - Dwiyantari, Teresia Nina; Rahyadi, Irmawan; Aras, Muhammad (International Review of Management and Marketing, 2026)
Online secondary markets have evolved into digitally mediated consumption ecosystems where consumers seek economic value, identity expression, and community interaction. However, empirical evidence on the factors driving participation in hobby-based online secondary markets remains limited. This study examines the effects of perceived value, trust, perceived risk, and social influence on consumer participation, investigates the moderating role of hobby involvement, and explores generational differences between Generation Z and Millennials. Data were collected in Indonesia from January to March 2026 through an online survey of 348 Generation Z and Millennial consumers with prior experience in online secondary markets. Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA) were employed to test the proposed model. The findings indicate that perceived value is the strongest driver of consumer participation, followed by trust and social influence, while perceived risk negatively influences participation. Hobby involvement weakens the effects of perceived value and social influence, suggesting that highly involved consumers are motivated more by intrinsic interest than by utilitarian benefits. Multi-group analysis further shows that Millennials are more value-oriented, whereas Generation Z consumers are more socially influenced.